Suppressing phagocyte activation by overexpressing the phosphatidylserine lipase ABHD12 preserves sarmopathic nerves - Caitlin B. Dingwall; Yo Sasaki; Amy Strickland; Tong Wu; Daniel W. Summers; A. Joseph Bloom; Aaron DiAntonio; Jeffrey Milbrandt (iScience)
Summary: Programmed axon degeneration (AxD) is a hallmark of many neurodegenerative diseases. In healthy axons, NMNAT2 inhibits SARM1, the key executioner of AxD, to keep it from depleting NAD+ and triggering axon destruction. AxD was assumed to be governed by axon-intrinsic mechanisms, independent of external factors. However, using a human disease model of neuropathy caused by hypomorphic NMNAT2 mutations resulting in chronic SARM1 activation, we demonstrated that neuronal SARM1 can initiate macrophage-mediated axon elimination long before stressed-but-viable axons would otherwise succumb to intrinsic metabolic failure. Chronic SARM1 activation causes axonal blebbing and disrupts phosphatidylserine (PS), a signaling molecule that promotes axon engulfment by macrophages. Neuronal expression of ABDH12, a PS lipase, reduces macrophage activation, preserves axons, and rescues motor function in this model, suggesting that PS dysregulation is an early SARM1-dependent axonal stress signal. Blocking macrophage-mediated axon elimination could be a promising therapeutic strategy for SARM1-dependent neurological diseases.